Validation of Siddha Diagnostic Procedure of Manikkadai nool for Gunmam Patients at Government Siddha Medical College & Hospital, Palayamkottai - Rakulini, R.; Rajarajeshwari, A.; Victoria, S. (Journal of Complementary and Alternative Medical Research, 2019)
Introduction: Siddha Medicine is a system of traditional medicine originating in ancient Tamil Nadu in South India and Sri Lanka. Traditionally, it is taught that the siddhas laid the foundation for this system of medicine. Siddha system has a unique diagnostic method to identify the diseases and their causes. Manikkadai Nool is one of the diagnostic tool. It is explained in the Agasthiyar Soodamani Kajiru Soothiram by Saint Veadammamuni in Pathinen Siddhar Naadi Nool. Aim: The primary aim of this study was to validate the Siddha diagnostic procedure of Manikkadai nool for gunmam patients. Study Setting: Government Siddha Medical College, Palayamkottai from April to August 2019. Methodology: It is an observational study. After identifying the eligible subjects, Data will be collected by using the interview administrated questionnaire & relevant data will be collected by measurement. Collected data were processed and statistically analysed by a simple statistical method using Microsoft Excel. Results and Discussion: Gunmam symptoms are included in 10, 9 ½, 8 ¾, 8, 7 ½, 7, 6 ½ & 6 ¼ Manikkadai measurements according to the siddha literatures. Researcher has been divided the gunmam conditions as mild moderate and severe condition according to the evidence of literatures, Researcher has been included Premonitory symptoms as Mild Condition, Common signs and symptoms as Moderate Condition and complications as Severe condition. Mild condition is in 10-9 fbs Manikkadai measurements. Moderate condition is in 8 ¾-7 ¾ fbs Manikkadai measurements. Severe condition is in 7 ½-6 ½ > Manikkadai measurements. 55% (11) of right hand Manikkadai measurements in male and 53% (16) of Right hand Manikkadai measurements in female have been correlated with the siddha literatures in the diagnosis of gunmam. Pearson correlation value implies that negative correlation between the chronicity of gunmam and Manikkadai measurement. This data showed the negative relationship between the severity of gunmam, & manikkadai measurements. Conclusion: Majority of the gunmam subjects were females (60%). The maximum number of subjects was observed in Pitha Kaalam. Majority of the gunmam subjects had vali azhal naadi (38%) and azhal vali naadi (32%). Nei kuri was observed as vali azhal & azhal vali in gunmam subjects. Siddha Physicians could be diagnosed the gunmam fifty percentage with the help of Manikkadai measurements. Pearson correlation value implies that negative correlation between the chronicity of gunmam and Manikkadai measurement. This data showed the negative relationship between the severity of gunmam & manikkadai measurements. Out of 50 gunmam subjects, 45 were in the assumed assessment criteria range. So further study is essential to validate this assumed assessment of criteria of manikkadai measurement in diagnosis of gunmam.
Keywords: Manikkadai Nool; Siddha; Diagnostic methods; Traditional; Medicine; Gunmam; Peptic ulcer